William E. Humphrey papers - Humphrey, William E. (William Ewart), 1862-1934.; United States. Federal Trade Commission
Correspondence, printed copies of Humphrey's speeches as U.S. representative, an original illustration by Clifford Kennedy Berryman, and records of the U.S. Federal Trade Commission. Subjects include cases before the commission, Humphrey's dissenting opinions, and his removal from the commission by Franklin D. Roosevelt. Correspondence with Theodore Roosevelt relates to Roosevelt's political conflicts within the Republican Party, his relations with William H. Taft and others following the secession of the Progressive Party from the Republican Party in 1912, and Roosevelt's advocacy of universal military training. Other correspondents include Warren G. Harding, Charles Evans Hughes, Thomas R. Marshall, and Harlan Fiske Stone.
Lawyer, U.S. representative from Washington, and member of the U.S. Federal Trade Commission.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Berryman, Clifford Kennedy, -- 1869-1949.; Harding, Warren G. -- 1865-1923 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Marshall, Thomas R. -- 1854-1925 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Theodore, -- 1858-1919.; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Stone, Harlan Fiske, -- 1872-1946 -- Correspondence; Taft, William H. -- 1857-1930.; Progressive Party (1912); Republican Party (U.S. : 1854- ); Draft -- United States; United States -- Commercial policy; United States -- Politics and government -- 1901-1953.; Lawyers; Public officials; Representatives, U.S. Congress -- Washington (State)